La decisión de escuchar música grabada en Colombia: Un enfoque microeconométrico - José A. Bermúdez Trivi\~no; Lina M. Medina Hurtado; Luis F. Aguado Quintero (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
– This paper purpose is to determine the variables that could influence the individual observable decision of listening to recorded music in Colombia. To do so, probit models are estimated using micro-data from the Encuesta de Consumo Cultural 2008 [Cultural Consumption Survey 2008 ]. Empirical results show that individuals with higher education that take cultural courses and workshops, and belong to medium and high socio-economic strata, are those with the highest probability of listening to recorded music. Additionally, self-identified individuals as African-Colombian-descendent resent the lowest likelihood. This paper contributes to the scarce empirical literature on the determinants of cultural participation in Latin America.
Keywords: Z11; D12; C25; 330; recorded music; cultural participation; probit models; Colombia